Environment and the developing world : principles, policies, and management - Gupta, Avijit. 4 0 16; Asher, Mukul G.; 5 (Chichester ;;New York : Wiley, 1998)
Environment and the Developing World brings together the various aspects of environmental studies and management (earth and natural sciences, engineering and economics) as they relate to the developing world. It discusses environmental issues as well as the techniques and infrastructure for their management at various levels: global, national and local. The examples range from global warming and ozone depletion to the management of water resources and indoor air pollution. The book stresses the interrelated and interdisciplinary nature of environment, discusses the concept of sustainable development, explores the role of non-governmental organisations, and evaluates the importance attributed by international and multilateral organisations to monitoring environmental aspects of development projects. It critically reviews various economic, social and regulatory policies which address environmental issues. The different disciplines of the two authors (a physical geographer and a public policy economist) help to maintain the balanced and interdisciplinary nature of the book. Written primarily for advanced undergraduates, this is a stimulating text for any environment related course. Written in simple language and avoiding unnecessary jargon the book explains clearly the technical aspects of environmental management. Profuse illustrations, a large number of examples from a range of geographical areas, boxed case studies and stimulating exercises make the book attractive and comprehensive. All these features make the book a unique teaching tool in environmental management in the developing world.
Includes bibliographical references (p. [333]-344) and index.
Keywords: 2 -- 0; 6; Environmental policy;Environmental policy -- Developing countries.;Tropics. -- 20; Economic policy.;Economic policy.;Environmental conditions. -- Developing countries;Tropics;Tropics -- 20; 2